2002
DOI: 10.1046/j.1440-1746.2002.02797.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin and Helicobacter pylori infection in children: A sero‐epidemiologic study in Korea

Abstract: Serum ferritin levels are reduced in children with H. pylori infection. The H. pylori infection may lead to iron deficiency in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
2
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 23 publications
(36 reference statements)
7
72
2
6
Order By: Relevance
“…These range in severity from mild gastritis to duodenal and gastric ulcers and two forms of gastric malignancy, mucosa-associated lymphoid tissue lymphoma and adenocarcinoma (7,22,46). Additionally, H. pylori infection has been linked to iron deficiency anemia (IDA), particularly in children and premenopausal women (5,53). Clinical evidence suggests that there are multiple mechanisms whereby H. pylori infection leads to IDA, either through the induction of impaired iron absorption by the host or through competition for the limited iron stores that are present (4).…”
mentioning
confidence: 99%
“…These range in severity from mild gastritis to duodenal and gastric ulcers and two forms of gastric malignancy, mucosa-associated lymphoid tissue lymphoma and adenocarcinoma (7,22,46). Additionally, H. pylori infection has been linked to iron deficiency anemia (IDA), particularly in children and premenopausal women (5,53). Clinical evidence suggests that there are multiple mechanisms whereby H. pylori infection leads to IDA, either through the induction of impaired iron absorption by the host or through competition for the limited iron stores that are present (4).…”
mentioning
confidence: 99%
“…The study also showed that H. pylori infection can lead to decreased of serum ferritin and increased of TIBC levels. Parkinson [15].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have demonstrated an association between H. pylori infection and anemia, ID, and IDA, although the mechanisms of the interactions have not been well defined [13,[57][58][59][60] [41,69] and reduced ascorbic acid secretion in the gastric mucosa [70,71] may lead to reduced iron absorption since they are essential for alimentary iron absorption; they not only convert ferric iron to the ferrous form, which maintains solubility at the alkaline pH of the duodenum, but also chelates with ferric chloride that is also stable at a pH >3. Uptake of iron by H. pylori is also suggested [72].…”
Section: H Pylori and Iron Deficiency Anemiamentioning
confidence: 99%
“…Iron absorption from ferrous fumarate was compared with that from a highly bioavailable, water-soluble iron compound (ferrous sulfate) in a randomized, crossover study using a double stable-isotope technique. Incorporation of 57 Fe and 58 Fe into erythrocytes 14 days after administration was used as an index of iron absorption [80]. The study noted geometric mean of iron absorption from ferrous sulfate and ferrous fumarate to be 19.7% and 5.3% respectively (P < 0.0001; n = 12) before treatment and 22.5% and 6.4% respectively after treatment (P < 0.0001; n = 11) of H. pylori-infected children ( Table 2).…”
Section: H Pylori and Iron Absorptionmentioning
confidence: 99%